The development and validation of an LC-MS/MS method for the quantification of ertapenem in human plasma: application to paediatric XDR-TB case studies - Mshayise, Nelisiwe (Stellenbosch : Stellenbosch University, 2026)
Thesis (MSc Pharmacology)--Stellenbosch University, 2025.